Neurogenic effects on the palatopharyngeal muscle in patients with obstructive sleep apnoea: a muscle biopsy study. Issue 10 (October 1992) - Edström, L; Larsson, H; Larsson, L
Abstract : Muscle biopsies from the palatopharyngeal muscle of eight patients with obstructive sleep apnoea were performed during uvulopalatopharyngoplasty. Control biopsies were performed during tonsillectomy in seven control patients with no history of symptoms suggesting obstructive sleep apnoea. The diagnosis was based on the patient's history and a whole night recording of arterial oxygen saturation and respiration movements. The mean number of oxygen desaturations > or = 4% per sleeping hour was 39 (range 7-80) in patients with obstructive sleep apnoea. In the control patients the occurrence of muscle fibre type and size relation between type I and type II fibres were comparable to what is found in the quadriceps femoris muscle, but the mean size of the fibres was < 25% of what is found in limb muscles. All biopsies from patients with obstructive sleep apnoea showed abnormalities. Atrophy with a fascicular distribution, increased number of angulated atrophic fibres, a twin or multiple peak distribution of the fibre size spectra, and an abnormal distribution of fibre types in many muscle fascicles corresponding to "type grouping" all points to a neurogenic alteration. This neurogenic lesion may be a primary phenomenon or secondary to the trauma of repetitive and prolonged stretching of the pharyngeal structures during apnoeas. A disturbance of the function of the dilating muscles of the upper airway may be important in causing the abnormal airway collapse seen in obstructive sleep apnoea.